Kinesin KIF4A transports integrin β1 in developing axons of cortical neurons - Heinzt, Tristan (2014)
CNS axons have poor regenerative ability compared to PNS axons, and mature axons regenerate less well than immature embryonic axons. The loss of regenerative ability with maturity is accompanied by the setting up of a selective transport filter in axons, restricting the types of molecule that are present. We confirm that integrins (represented by subunits β1 and α5) are present in early cortical axons in vitro but are excluded from mature axons. Ribosomal protein and L1 show selective axonal transport through association with kinesin kif4A; we have therefore examined the hypothesis that integrin transport might also be in association with kif4A. Kif4A is present in all processes of immature cortical neurons cultured at E18, then downregulated by 14 days in vitro, coinciding with the exclusion of integrin from axons. Kif4a co-localises with β1 integrin in vesicles in neurons and non-neuronal cells, and the two molecules co-immunoprecipitate. Knockdown of KIF4A expression with shRNA reduced the level of integrin β1 in axons of developing neurons and reduced neurite elongation on laminin, an integrin-dependent substrate. Overexpression of kif4A triggered apoptosis in neuronal and non-neuronal cells. In mature neurons expression of kif4A-GFP at a modest level did not kill the cells, and the kif4A was detectable in their axons. However this was not accompanied by an increase in integrin β1 axonal transport, suggesting that kif4A is not the only integrin transporter, and that integrin exclusion from axons is controlled by factors other than the kif4A level.